Storage lipid dynamics in somatic embryos of Norway spruce (Picea abies): histochemical and quantitative analyses - Grigová, Magdalena; Kubes, Martin; Drázná, Nikola; Rezanka, Tomás; Lipavská, Helena (Tree physiology, 2007)
Adequate storage compounds are a prerequisite for successful development during the later stages of somatic embryogenesis; however, the critical amount of reserves below which somatic embryos fail to mature and germinate has not been determined. We analyzed storage lipids during Norway spruce (Picea abies (L.) Karst.) somatic embryogenesis. As maturation progressed, lipids, which were stored as lipid bodies in the cytoplasm, were localized first in suspensor cells of the early embryos, and later in the embryonic root pole, superficial layers of the hypocotyl and in cotyledons. The concentration of total lipids exhibited marked variation, with values peaking during cotyledon development and then decreasing during maturation. Linoleic (18:2), oleic (18:1), palmitic (16:0) and 5,9-octadecenic (5,9-18:2) acids were the most abundant fatty acids in embryos. As embryos developed, linoleic acid concentration increased slightly, whereas oleic acid concentration decreased. Oleic acid was the most prominent component of the fatty acid spectrum in isolated dormant zygotic embryos and megagametophytes. Addition of 5% polyethylene glycol to the medium during somatic embryo maturation caused a shift in the fatty acid spectrum toward that of zygotic embryos. During maturation, changes in the exogenous carbohydrate supply had no significant effect on total lipid concentration in mature embryos. A marked decrease in lipid concentration was detected during desiccation, indicating the importance of adequate lipid reserves during this developmental stage. The lipid content of zygotic embryos differed considerably with harvest year and location, suggesting that zygotic embryo data cannot be an indicator of somatic embryo quality.
Keywords: Carbohydrate Metabolism; embryonální vývoj; kultivační techniky; Picea; semena rostlinná; metabolismus lipidů; metabolismus sacharidů; Seeds; Embryonic Development; Lipid Metabolism; smrk; Culture Techniques; voda; Water